2012
DOI: 10.1155/2012/196841
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Heat Resistance of Food Borne PathogensCampylobacter jejuni, Escherichia coli, andSalmonella typhimuriumon Chicken Breast Fillet during Cooking

Abstract: The aim of this research was to determine the decimal reduction times of bacteria present on chicken fillet in boiling water. The experiments were conducted withCampylobacter jejuni, Salmonella, andEscherichia coli. Whole chicken breast fillets were inoculated with the pathogens, stored overnight (4 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…However, it is demonstrated that the assumed inactivation of pathogenic bacteria in meat and meat preparations might be overestimated. This phenomenon was also shown by other studies (Bergsma et al, 2007;de Jong et al, 2012, Roccato et al, 2015. Although many data on heat resistance in buffer systems are available which show that heat resistance of microorganisms can vary depending on the species, strain and physiological state of microbial cells, data in actual foods upon consumer-based cooking processes are comparatively scarce (Doyle and Mazzotta, 2000;Juneja et al, 2001;Lianou et al, 2006;Lianou and Koutsoumanis, 2013;Nguyen et al, 2006;Smelt and Brul, 2014).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, it is demonstrated that the assumed inactivation of pathogenic bacteria in meat and meat preparations might be overestimated. This phenomenon was also shown by other studies (Bergsma et al, 2007;de Jong et al, 2012, Roccato et al, 2015. Although many data on heat resistance in buffer systems are available which show that heat resistance of microorganisms can vary depending on the species, strain and physiological state of microbial cells, data in actual foods upon consumer-based cooking processes are comparatively scarce (Doyle and Mazzotta, 2000;Juneja et al, 2001;Lianou et al, 2006;Lianou and Koutsoumanis, 2013;Nguyen et al, 2006;Smelt and Brul, 2014).…”
Section: Discussionmentioning
confidence: 56%
“…This increases the risk of survival and cross-contamination of pathogenic micro-organisms in undercooked meat (Sampers et al, 2012). Besides, Bergsma et al (2007) and de Jong et al (2012) showed in their studies unsuspected survival of pathogens during consumer style cooking techniques. Therefore, the objective of the present study is to evaluate the effect of simulated home pan frying of raw meat and meat preparations of different animal species on the thermal inactivation of pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of one of these studies (1), which reported a remarkably high D-value, stated that their study had limitations: variations in measurement of the chicken fillet surface temperature caused variations in the survival data. The other study (7), presented as a poster in a conference, has not yet been published in a peer-reviewed journal. Thus, there were no more details available about the methods used or the study's limitations.…”
Section: Resultsmentioning
confidence: 99%
“…Salmonella species in foods of animal origin are most frequently considered to be associated with the foodborne pathogen outbreaks. Improper cooking, inadequate storage, cross-contamination and use of raw ingredients in the preparation of food are the most common factors contributing to outbreaks [2,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%